STRATEGI NOTARIS DALAM MENJAGA INDEPENDENSI DAN PROFESIONALISME DI TENGAH TEKANAN KLIEN - Qorib, Syarif Facthul; Sudirman, M.; Djaja, Benny (Yayasan Education and Social Center, 2025)
This study aims to explore the strategies employed by notaries to maintain independence and professionalism amid client pressure. Using a qualitative approach with a case study method, data were collected through in-depth interviews, non-participant observation, and documentation involving active notaries in major cities. The findings reveal that notaries apply various strategies, including assertively rejecting inappropriate client requests, referring to the Code of Ethics and Notary Law, consulting with professional peers, and managing pressure through professional communication. Assertive refusals are delivered politely with legal reasoning, while references to regulations strengthen their position. Peer consultation serves as a collective ethical mechanism, and communicative approaches help clients understand the legal limits of notarial roles. These strategies are adaptive, contextual, and demonstrate a synergy between legal norms, ethical awareness, and interpersonal skills. The study concludes that notaries can uphold professionalism and independence through a combination of legal, ethical, and communicative approaches. These findings are expected to contribute to notarial professional development and the enhancement of ethical standards in notarial practice.